The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/idh.12440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral health promotion programmes on adolescents’ oral health‐related quality of life: A systematic review

Abstract: ObjectiveTo evaluate the effects of oral health promotion programmes (OHPP) on adolescents' oral health‐related quality of life (OHRQoL).MethodsAn electronic search was performed in five databases (MEDLINE via PubMed, Scopus, Virtual Health Library, Web of Science, Cochrane, Grey Literature databases), and specific indexers were used in the manual search. Clinical/community trials, cross‐sectional or cohort studies, published in any language, were included. Studies meeting the inclusion criteria were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
11
0
2
Order By: Relevance
“…A systematic review has shown positive effects of oral health promotion programs on OHRQoL 6 evaluating educational preventive programs, school‐based dental programs, and outcomes of dental caries, gingivitis, and atraumatic restorative treatment. Concerning TDI, only one article has evaluated cases of TDI treated in individuals aged between 7 and 13 years in the Dentoalveolar Trauma Care Service, 21 but it did not assess the pre‐ and post‐treatment changes in OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review has shown positive effects of oral health promotion programs on OHRQoL 6 evaluating educational preventive programs, school‐based dental programs, and outcomes of dental caries, gingivitis, and atraumatic restorative treatment. Concerning TDI, only one article has evaluated cases of TDI treated in individuals aged between 7 and 13 years in the Dentoalveolar Trauma Care Service, 21 but it did not assess the pre‐ and post‐treatment changes in OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are more sustainable and can reduce inequalities through actions directed at the underlying determinants to improve oral health 4 . There is evidence that preventive approaches and oral health promotion programs are more effective, both clinically and in terms of cost‐effectiveness, than standard dental care 4–6 . Benefits from an oral health intervention program are not only clinical, but may be reflected in improvements in the OHRQoL 6 …”
Section: Introductionmentioning
confidence: 99%
“…Finalmente, existe en odontología, un espacio desde la promoción de la salud y la prevención de la enfermedad, que puede y debe incorporarse dentro del ejercicio profesional durante la era de la pandemia, factible sin involucrar aerosoles y controlando por aislamiento social el riesgo de infección por COVID-19 en el equipo profesional y en los pacientes, pero a su vez, favoreciéndose de la efectividad demostrada de medidas de educación en salud oral y medidas preventivas para el control de la caries dental, principalmente en los grupos poblacionales de mayor riesgo a esta patología oral, como son los preescolares, escolares y adultos mayores, favoreciéndose también la aplicación de la teleodontología 178,[206][207][208][209][210][211][212][213][214] .…”
Section: Fuerte a Favorunclassified
“…Oral health is considered an integral part of general health as well as quality of life [6][7][8]. The most common oral diseases are caries and periodontal diseases [9,10], complex diseases of infectious nature, which are caused by the imbalance between the host and the host microorganisms of the biofilm in the oral cavity [11].…”
Section: Introductionmentioning
confidence: 99%